Hottentot Venus a novel - Chase-Riboud, Barbara (Doubleday, a division of Random House, Inc., 2003)
"Born in the colony of Good Hope, South Africa, in 1789, Sarah Baartman was taken to London at the age of twenty by an English surgeon, who promised her fame and fortune. Dubbed the ₃Hottentot Venus, ₄ she was paraded naked in Piccadilly in a freak-show exhibition and subjected to the unabashed stares and crude comments of the British public, which resulted in a sensational trial for her custody by British abolitionists."--Cover.